Dante's deadly sins : moral philosophy in Hell - Belliotti, Raymond A., 1948-; Wiley InterScience (Online service) (Malden, MA : Wiley-Blackwell, 2011)
Dante's Deadly Sins is a unique study of the moral philosophy behind Dante's master work that considers the Commedia as he intended, namely, as a practical guide to moral betterment. Focusing on Inferno and Purgatorio, Belliotti examines the puzzles and paradoxes of Dante's moral assumptions, his treatment of the 7 deadly sins, and how 10 of his most powerful moral lessons anticipate modern existentialism. Analyzes the moral philosophy underpinning one of the greatest works of world cultureSummarizes the Inferno and Purgatorio, while underscoring their moral implicationsExplains and evaluates D.
Inferno -- Purgatorio -- The notion of desert and the law of contrapasso -- Paradoxes and puzzles : Virgil and Cato -- The seven deadly sins -- Dante's existential moral lessons.
Includes bibliographical references and index.
Print version record.
Keywords: Dante Alighieri, -- 1265-1321.; Dante Alighieri, -- 1265-1321 -- Ethics; Dante Alighieri, -- 1265-1321; Divina commedia (Dante Alighieri); Deadly sins in literature; Hell in literature; Dante Alighieri; Dante Alighieri -- Ethics; Literature; Deadly sins in literature; Ethics; Hell in literature; Electronic books